Body image screening for cancer patients undergoing reconstructive surgery. Issue 8 (6th February 2014) - Fingeret, Michelle Cororve; Nipomnick, Summer; Guindani, Michele; Baumann, Donald; Hanasono, Matthew; Crosby, Melissa
Abstract Objectives Body image is a critical issue for cancer patients undergoing reconstructive surgery, as they can experience disfigurement and functional impairment. Distress related to appearance changes can lead to various psychosocial difficulties, and patients are often reluctant to discuss these issues with their healthcare team. Our goals were to design and evaluate a screening tool to aid providers in identifying patients who may benefit from referral for specialized psychosocial care to treat body image concerns. Methods We designed a brief four‐item instrument and administered it at a single time point to cancer patients who were undergoing reconstructive treatment. We used simple and multinomial regression models to evaluate whether survey responses, demographic, or clinical variables predicted interest and enrollment in counseling. Results Over 95% of the sample (n = 248) endorsed some concerns, preoccupation, or avoidance because of appearance changes. Approximately one‐third of patients were interested in obtaining counseling or additional information to assist with body image distress. Each survey item significantly predicted interest and enrollment in counseling. Concern about future appearance changes was the single best predictor of counseling enrollment. Sex, age, and cancer type were not predictive of counseling interest or enrollment. Conclusions We present initial data supporting use of the Body Image Screener for Cancer Reconstruction. Our findings suggest benefits of administering this tool to patients presenting for reconstructive surgery. It is argued that screening and treatment for body image distress should be provided to this patient population at the earliest possible time point. Copyright © 2014 John Wiley & Sons, Ltd.